Análise da caminhabilidade de idosos a partir de suas rotas preferenciais : um estudo de caso no Bairro Floresta - Clarissa Pontes Melo (2021)
The work developed here contributes to discussions about the walkability of the elderly in Brazil, where such concepts have not yet been widely studied and have a long process to be implemented. Thus, the dissertation aims to understand whether the use of sidewalks by the elderly with a low order motif is related to the quality of the attributes of the urban space. To this end, a walkability index aimed at the elderly was systematized, based on the adaptation of existing walkability indexes, and on the use of the main indicators related to walking by the elderly, considering the Brazilian reality. To apply the index in question, Floresta Neighborhood was chosen, where the necessary information on the composition of the 11 selected walkability indicators was collected and mapped. Furthermore, through research, the priority routes of elderly pedestrians were identified for reasons of low order functions. Through the data obtained, application of the Spearman and Chi-Square tests and analysis on maps, we verified the degree of correlation between the walkability indicators and their association with the walkability index and the preferential routes of the elderly. Additionally, the result of the statistical determination of spatial clusters was carried out based on the result of the walkability index. The Floresta neighborhood was then characterized from the analysis of the indicators and grouped into zones, using clustering methods. As a result of the dependency tests, it was possible to infer that the choice of routes for elderly pedestrians, in different magnitudes, has dependence on the following walkability indicators: width of sidewalks, slope, afforestation, proximity to squares and parks, existence of lane pedestrians, aesthetics and visual perception, diversity of land use, concentration of services and finally, the walkability index, in the Floresta neighborhood. However, it is independent of the condition of the pavement and the useful width of the sidewalk in this context. Additionally, it was found that most of the walkability indicators are correlated with each other.